Penerapan Peraturan Emisi pada Penurunan Emisi Gas Rumah Kaca dari Kendaraan Bermotor di Indonesia - Mubarak, Naufal Ramadhan; Ratnasari, Juni (Bacarita Law Journal, 2025)
This article analyzes the impact of emission regulations on reducing greenhouse gas emissions from motor vehicles in Indonesia. The study aims to evaluate the implementations of legislation governing vehicle emissions to support reduction targets, aligned with Indonesia's commitment to decrease emissions by 29% by 2030 under the Paris Agreement. This research employs a qualitative method with a juridical-normative approach, relying on secondary data, including regulations, statistics, and related literature. Data were collected through document studies, literature analysis, and reviews of official statistical data. The findings indicate that implementing emission regulations has positively contributed to reducing vehicle emissions, despite existing challenges such as gaps in monitoring private vehicles and motorcycles that are not required to undergo periodic emissions testing. Increasing the ambition of emission standards, such as adopting Euro 5 or Euro 6, is deemed crucial to achieving significant reductions. The study finds that the success of these regulations heavily depends on consistent oversight, innovation in the automotive industry, and public support. These findings emphasize the necessity for collaboration between the automotive industry, the government, and the public to enhance awareness and compliance with emission regulations. Implementing environmental taxes and penalties could serve as alternatives to encourage compliance. With strict regulations and effective collaboration, reducing vehicle emissions is expected to contribute significantly to mitigating global climate change.